DEVELOPMENT OF NANOSILICA MODIFIED HIGH VOLUME FLY ASH ROLLER COMPACTED RUBBERCRETE FOR PAVEMENT APPLICATION. - ADAMU, MUSA (2018)
The major problems related to roller compacted concrete (RCC) pavement are high rigidity, lower tensile strength which causes tendency of cracking due to thermal or plastic shrinkage, flexural and fatigue loads.